Cross-Linking Mast Cell Specific Gangliosides Stimulates the Release of Newly Formed Lipid Mediators and Newly Synthesized Cytokines - Edismauro Garcia Freitas Filho; Elaine Zayas Marcelino da Silva; Camila Ziliotto Zanotto; Constance Oliver; Maria Célia Jamur (Mediators of Inflammation)
Mast cells are immunoregulatory cells that participate in inflammatory processes. Cross-linking mast cell specific GD1b derived gangliosides by mAbAA4 results in partial activation of mast cells without the release of preformed mediators. The present study examines the release of newly formed and newly synthesized mediators following ganglioside cross-linking. Cross-linking the gangliosides with mAbAA4 released the newly formed lipid mediators, prostaglandins D2 and E2, without release of leukotrienes B4 and C4. The effect of cross-linking these gangliosides on the activation of enzymes in the arachidonate cascade was then investigated. Ganglioside cross-linking resulted in phosphorylation of cytosolic phospholipase A2 and increased expression of cyclooxygenase-2. Translocation of 5-lipoxygenase from the cytosol to the nucleus was not induced by ganglioside cross-linking. Cross-linking of GD1b derived gangliosides also resulted in the release of the newly synthesized mediators, interleukin-4, interleukin-6, and TNF-α. The effect of cross-linking the gangliosides on the MAP kinase pathway was then investigated. Cross-linking the gangliosides induced the phosphorylation of ERK1/2, JNK1/2, and p38 as well as activating both NFκB and NFAT in a Syk-dependent manner. Therefore, cross-linking the mast cell specific GD1b derived gangliosides results in the activation of signaling pathways that culminate with the release of newly formed and newly synthesized mediators.